Conceptual Miscalculations of Aggressive Myth-Making - Vasyl Struhatskyi (Cхід, 2018)
The author continues the philosophical study of manipulative influence on the mass consciousness, which is the basic component of the aggression of the Russian Federation against Ukraine.